2019
DOI: 10.1088/1741-4326/ab3f87
|View full text |Cite
|
Sign up to set email alerts
|

MARS-F modeling of post-disruption runaway beam loss by magnetohydrodynamic instabilities in DIII-D

Abstract: A drift orbit model for relativistic test electrons has been incorporated into the MARS-F code (Liu et al 2000 Phys. Plasmas 7 3681), in order to study the runaway electron (RE) behavior in the presence of magneto-hydrodynamic perturbations computed by MARS-F. By implementing the model directly into the MARS-F curve-linear magnetic coordinates, maximal accuracy in representing the full field perturbation is preserved. The updated code is utilized to study the high current RE beam loss in a post-disruption DIII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
49
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 33 publications
9
49
0
Order By: Relevance
“…8 shows the radial structure of plasma displacement on the direction normal to flux surfaces (ξ n ) decomposed into different poloidal harmonics. The displacement is also localized near q = 2, which is in agreement with the linear results found with MARS-F [16].…”
Section: Linear Simulation Of (21) Resistive Kink Modesupporting
confidence: 90%
See 1 more Smart Citation
“…8 shows the radial structure of plasma displacement on the direction normal to flux surfaces (ξ n ) decomposed into different poloidal harmonics. The displacement is also localized near q = 2, which is in agreement with the linear results found with MARS-F [16].…”
Section: Linear Simulation Of (21) Resistive Kink Modesupporting
confidence: 90%
“…The simulation is based on a DIII-D shot 177040, in which a large RE current is generated from the avalanche after the initial disruption, and finally leads to a "second disruption" when the edge safety factor (q a ) approaches 2, and causes the sudden loss of all RE [8]. The linear simulation shows the dominance of the (2,1) kink mode near the edge, in agreement with previous work using MARS-F [16]. In the nonlinear simulation, it is found that as the (2,1) resistive kink mode grows exponentially, more than 95% of the REs can get lost to the wall due to the breaking of flux surfaces and formation of stochastic field lines.…”
Section: Introductionsupporting
confidence: 80%
“…A prompt (on a µs time scale) RE loss domain is computed assuming n = 1 internal kink mode eigenfunction using a drift orbit model for relativistic test electrons recently incorporated into the MARS-F code [84]. Almost no RE loss is found when perturbations of the poloidal magnetic field with a magnitude δB p = 0.1 G are applied at the HFS inside the DIII-D vessel as shown in Figure 10(d).…”
Section: Mars-f Ideal Modellingmentioning
confidence: 99%
“…Experiments aimed at mitigating tokamak disruptions with massive material injection (gas or pellets) have long sought unsuccessfully to exceed the so-called Rosenbluth density to maintain E < E crit even at postthermal quench temperatures [3][4][5]. Injection of either high-Z (Ne, Ar, Kr, Xe) [6,7] or low-Z (He, D 2 ) [7,8] material into an existing runaway electron beam has also been pursued, with D 2 injection showing strong promise experimentally for benign termination of a runaway electron beam by a kink instability, supported by extended-MHD modelling [9][10][11], which has been extended to ITER scenarios [12]. Strategies to prevent the formation of a mature RE beam involve enhancing transport of the seed REs in physical or momentum space, e.g., by stochastic magnetic fields [13][14][15][16][17][18] or wave-particle interactions [19,20], to produce a loss rate that exceeds the avalanche growth rate.…”
Section: Introductionmentioning
confidence: 99%